Numerične simulacije toka tekočine in delcev v granulatorju z lebdečim slojem - Kevorkijan, Luka (Anali PAZU, 2022)
The objective of this study was to determine the distribution of air flow on a distributor plate of a laboratory fluid bed granulator. The uniform spatial distribution of particles is important for the granulation process. Instead of the current approaches to scaling the process parameters for air flow rate based on the concept of apparent air velocity, it would be desirable to also consider the distribution of air flow above the distributor, since the flow is not uniform. We have performed several numerical simulations of the air flow using computational fluid dynamics (CFD) and several two-way coupled simulations using CFD and the discrete element method (DEM), motivated by our confirmed assumption that particles affect the air flow distribution. We found that the air flow rate through the granulator affects the distribution of the air flow on the distributior, especially in the case of a loaded granulator.
Keywords: airflow distribution; computational fluid dynamics; discrete element method; distribution plate; fluidized bed; lebdeči sloj; metoda diskretnih elementov; porazdelitev pretoka zraka; računalniška dinamika tekočin; razdelilna plošča